A Murder in Ferrara - Benmelech, Moti (Women in Judaism, 2024)
The article, entitled “A Murder in Ferrara,” was originally published in Hebrew in the peer-reviewed journal Masakhet. It is the only scholarly study to date that deals directly with an honor killing within Jewish society, focusing on the murder of a Jewish woman by her brother in Ferrara in 1577 following a romantic relationship with a non-Jewish man. The article analyzes this case as an instance of extreme sexual and familial violence, examining the penetration of Mediterranean concepts of family honor into Jewish society and the attempt to translate these norms into internal Jewish legal and moral categories. It also discusses the sharp rabbinic criticism of such justifications and highlights the gendered dimensions of violence, honor, and communal boundaries in early modern Jewish life.